ACCESS TO PRESCHOOL EDUCATION - Nordonqulova, Marjona Jo‘rabek qizi; Tukhtamuratova , Zumrad Zarifboy qizi; Burkhanova, Ma’mura Gulyamovna (Innovative Development in Educational Activities, 2022)
Many parents know that the former child. However, this is not true, and the child needs daily confirmation that he really loves him. Love can be expressed in many ways – kind words are passed along with time and affirmation.